Evaluations of Potable Water Tanks Epoxy Coatings Performance Using Electrochemical Impedance Spectroscopic Method - Jasim, Haider Hadi (Al-Khwarizmi Engineering Journal, 2017)
Abstract  The aim of this paper is to investigate and discuss the mechanisms of corrosion of epoxy coatings used for potable water tanks. Two distinct types of Jotun epoxy coatings: Tankguard 412 contained polyamine cured epoxy and Penguard HB contained polyamide cured epoxy, were tested and studied using the electrochemical impedance spectroscopic (EIS) method. The porosity of epoxy coatings was determined using EIS method. The obtained results showed that the two epoxy coatings have excellent behavior when applied and tested in potable water of Basrah city. Polyamine is more resistance to water corrosion compared to polyamide curing epoxy and has high impedance values. Microscopic inspection after test showed that the polyamine cured epoxy has blistering while the surface of polyamide cured epoxy showed pitting and blisters.Keywords: Corrosion mechanism , epoxy coats, porosity, potable water, , EIS method.